Environmental changes during the Cretaceous-Paleogene mass extinction and Paleocene-Eocene Thermal Maximum: Implications for the Anthropocene - KELLER, G; MATEO, P; PUNEKAR, J; KHOZYEM, H; GERTSCH, B; SPANGENBERG, J; BITCHONG, AM; ADATTE, T (ELSEVIER SCIENCE BV, 2018)
The Cretaceous-Paleogene boundary (KPB) mass extinction (similar to 66.02 Ma) and the Paleocene-Eocene Thermal Maximum (PETM) (similar to 55.8 Ma) are two remarkable climatic and faunal events in Earth's history that have implications for the current Anthropocene global warming and rapid diversity loss. Here we evaluate these two events at the stratotype localities in Tunisia and Egypt based on climate warming and environmental responses recorded in faunal and geochemical proxies. The KPB mass extinction is commonly attributed to the Chicxulub impact, but Deccan vol-canism appears as a major culprit. New mercury analysis reveals that major Deccan eruptions accelerated during the last 10 ky and reached the tipping point leading up to the mass extinction. During the PETM, climate warmed rapidly by similar to 5 degrees C, which is mainly attributed to methane degassing from seafloor sediments during global warming linked to the North Atlantic Igneous Province (NAIP). Biological effects were transient, marked by temporary absence of most planktic foraminifera due to ocean acidification followed by the return of the pre-PETM fauna and diversification. In contrast, the current rapid rise in atmospheric CO2 and climate warming are magnitudes faster than at the KPB or PETM events leading to predictions of a PETM-like response as best case scenario and rapidly approaching sixth mass extinction as worst-case scenario. (C) 2017 International Association for Gondwana Research. Published by Elsevier B.V. All rights reserved.